KONSEP ULAMA DAN PROSES PENDIDIKANNYA: Pendekatan Metode Tafsir Maudhu’i bi al-Dirâyah - Subky, Badruddin H.; Husaini, Adian; Hafidhuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2015)
Abstract— The existence of islamic scholar in this world has an important meaning, because they have the highest position beside Allah SWT. If there is no scholar, then mens just like animals, but now days, the scholar faced by many pronlems and challenges. Now, Islamic scholar become more tittle, some of them died and some unactive. While Islamic boarding school and islamic university where the scholar produced still questioned. There for, this research has done by some source of problem. What is the criteria of islamic scholar in Qur’anic view ? How is the concept of islamic scholar education due to Qur’anic view? And how the application (ideal model) of scholar’s education on the perspective of Islamic education? This research using the qualitative method, by approaching of tafsir maudhu’i biddirayah. Which is the degree of ulama must be match with Al-Quran’s perspective. To sketch the concept of ulama education and its application, then this research was done at Badan Kerjasama Pondok Pesantren Indonesia (BKsPPI) as the conceptor of Ma’had “Aly (Islamic Boarding for University student). During this research, the writer found that in the terminologocal meaning, Ulama is slave of Allah SWT, the heir of the prophets, and has 11 criteria should be fulfilled by the ulama to be able the message of the prophet. The 11 criterias, are that the ulama should be afraid to Allah SWT and be a master in islamic sciences sourced from Al- Quran and Sunnah, also contemporer sciences sourced from natural sciences. With those 11 criterias and mastering the islamic sciences comprehensipand universally, hoped that Ulama be able to do their duty as a teacher, supervisor, develover, teaching the complete islamic knowledges to all people in the world. Ulama’s educations, from the observation of the concept of Ma’had Aly at BKsPPI, concluded that ideal of the Ulama’s education model is the system of Islamic boarding school, Ma’had Aly. Whereas, in BKsPPI, the application of Ma’had Aly is still in the concept area. Ideal concept of Ulama’s education which is being offered should be passed three points. Input, education process, and output. The input must have the criteria such as intelegencies, motivation/struggle, patient, facilities, the expert teacher, and continually process. The process is by create good management, good facilities, and good teacher, fit curriculum, professional procedure and process, and comprehensive evalution in the education institution. The output are the ulama who has the 11 criteria. For the stakeholder, have to offer the education for Ulama. Government, should make the good policy for successing the Ulama education. Keywords: education concept, education objectives, Islamic education, character education, character, akhlaq, values, morality